Homelessness and reentry: a multisite outcome evaluation of Washington State’s reentry housing program for high risk offenders - Lutze, Faith E. (Criminal justice and behavior, 2014)
Each year many offenders are released homeless putting them at great risk of being returned to prison. To reduce the likelihood of recidivism, Washington State implemented the Reentry Housing Pilot Program (RHPP) to provide housing assistance for high risk/high need offenders leaving prison without a viable place to live. This study provides a longitudinal (2008-2011), multisite outcome evaluation that considers how ex-offenders in the RHPP program (n = 208), who were provided housing and wraparound services, compared with similar offenders released with an elevated risk of homelessness while being traditionally supervised (n = 208). Findings show that the RHPP program was successful in significantly reducing new convictions and readmission to prison for new crimes, but had no significant effect on revocations. In addition, results showed that periods of homelessness significantly elevated the risk of recidivism for new convictions, revocations, and readmission to prison. The authors recommend that subsidized housing for high risk offenders become a central part of coordinated responses to reentry.